Upregulation of Oxytocin Receptor in the Hyperplastic Prostate - Li, Zhuo; Xiao, He; Wang, Kebing; Zheng, Yuelan; Chen, Ping; Wang, Xinghuan; DiSanto, Michael E.; Zhang, Xinhua (Frontiers in Endocrinology, 2018)
Background: The etiology of benign prostatic hyperplasia (BPH) is complex, both age and androgen are thought to be important. However, the failure of androgen blockade treatments suggests other paracrine/autocrine factors involved in BPH. Oxytocin was found to have a paracrine/autocrine role in prostate in recent years. The influence of BPH on prostatic oxytocin receptor (OTR) expression has never been studied. Material and Methods: A testosterone-estradiol induced rat model of BPH was developed and human hyperplastic prostate specimens were harvested. OTR, α1-adrenoreceptor subtypes (α1aARs, α1bARs, α1dARs) and nitric oxide synthase isoforms (eNOS and nNOS) were determined with real-time RT-PCR. OTR was further analyzed with Western-Blotting and histological examination. Subsequently, rat epithelial cells, human stromal cells and epithelial cells were cultured in vitro and treated with gradient concentrations of OT from 1 to 5 days. Cell proliferation was tested by Cell Counting Kit-8 and Flow CytoMetry. Results: The rat BPH model was validated with significant increased prostate weight. H-E stain showed different histopathology between human and rat BPH. Masson’s trichrome staining showed smooth muscle cells, epithelium cells and collagen fibers were simultaneously augmented in rat BPH model and human sample. OTR mainly localized in epithelium in rat prostate whereas it mainly localized in stroma in human prostate. OTR gene was upregulated 3.3-fold in rat BPH and 3.0-fold in human BPH, along with increased expression of 2.0-fold α1aARs and 3.0-fold eNOS for rat BPH and 5.0-fold α1aARs for human BPH. The expression of OTR protein was upregulated 1.4-fold in rat BPH and 3.9-fold in human BPH, respectively. The concentration of exogenous OT can accelerate proliferation of rat epithelial cell and human stromal cell but has no impact on human epithelial cell in vitro. Flow CytoMetry showed oxytocin could significantly increase G2/M period cell number. Conclusions: Our novel data showed a significantly and previously undocumented upregulation of OTR in both rat and human BPH. Moreover, exogenous oxytocin accelerates proliferation of rat prostate epithelial cell and human prostate stromal cell. It is suggested OTR is involved in the development of BPH and OT system could be a potential new target for the therapy of BPH.